Dynamics and consequences of nutrition-related microbial dysbiosis in early life: study protocol of the VITERBI GUT project - Tamarelle, Jeanne; Creze, Margaux M.; Savathdy, Vanthanom; Phonekeo, Sengrloun; Wallenborn, Jordyn; Siengsounthone, Latsamy; Fink, Günther; Odermatt, Peter; Kounnavong, Sengchanh; Sayasone, Somphou; Vonaesch, Pascale (Frontiers in Nutrition, 2023)
Introduction. Early life under- and overnutrition (jointly termed malnutrition) is increasingly recognized as an important risk factor for adult obesity and metabolic syndrome, a diet-related cluster of conditions including high blood sugar, fat and cholesterol. Nevertheless, the exact factors linking early life malnutrition with metabolic syndrome remain poorly characterized. We hypothesize that the microbiota plays a crucial role in this trajectory and that the pathophysiological mechanisms underlying under- and overnutrition are, to some extent, shared. We further hypothesize that a “dysbiotic seed microbiota” is transmitted to children during the birth process, altering infants’ microbiota composition and metabolic health. The overall objective of this project is to understand the precise causes and biological mechanisms linking prenatal or early life under- or overnutrition with the predisposition to develop overnutrition and/or metabolic syndrome in later life, as well as to investigate the possibility of a dysbiotic seed microbiota inheritance in the context of maternal malnutrition. Methods/Design. VITERBI GUT is a prospective birth cohort allowing to study the link between early life malnutrition, the microbiota and metabolic syndrome. VITERBI GUT will include 100 undernourished, 100 normally nourished and 100 overnourished pregnant women currently residing in Vientiane, Lao PDR. Women will be recruited during their third trimester of pregnancy and followed with their child until the child reaches the age of two. Anthropometric, clinical, metabolic and nutritional data are collected from both the mother and the infant. The microbiota composition of maternal and infant’s fecal and oral samples as well as maternal vaginal and breast milk samples will be determined using amplicon and shotgun sequencing. Epigenetic modifications and lipid profiles will be assessed in the infant’s blood at two years of age. We will investigate possible associations between metabolic health, epigenetics, and microbial changes. Discussion. We expect the VITERBI GUT project to contribute to the emerging literature linking early life microbiota, epigenetic changes and growth/metabolic health. We also hope this project will allow us to gain new (molecular) insights into the mechanisms linking malnutrition-induced early life dysbiosis to metabolic health in later life, opening new avenues for prevention using microbiota-targeted interventions in the future.